“Ele achou que ia ganhar um diploma também”: a experiência de mães estudantes e seus bebês, nos cursos de graduação de uma universidade pública - Torre, Larissa Cristina; Semenzato, Carolina de Campos (Universidade Federal de São Carlos, 2021)
Women had to fight to conquer the right of access to education, and only in the year 1879, in Brazil, women obtained the right to attend higher education. Despite this delay, when comparing the number of men and women graduating from Higher Education in Brazil, according to the Census of Higher Education 2019, published by the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (INEP), we note that the percentage of women graduating from higher education is greater. In addition, the 2016 Higher Education Census reveals that women represent 57.2% of the total number of students enrolled in undergraduate courses. However, even though thousands of women enter higher education every year and pregnancy is a natural biological process that can happen in a planned or unplanned way, higher education institutions still seem unprepared to deal with the situation of pregnant students, for which there is the need to continue advancing to make these women welcome. The present work sought to give voice and space to women who went through the experience of gestating a life while they were attending an undergraduate course. We had the participation of eight women who had their reports collected through video calls. The meetings were held by the Google Meet platform, with an average duration of one hour each, through a semi-structured interview. We consider these reports a first approach to the topic of pregnancy during graduation, a brief account of the context of UFSCar, a subject that, we believe, needs to continue to be debated by the entire university community.
“He thought he was going to earn a degree too”: the experience of student mothers and their babies in undergraduate courses
Keywords: Graduação; Gravidez; Alunas; Universidade pública; Graduation; Pregnancy; Public university; Female students; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL